Cardiopulmonary exercise testing for heart failure: pathophysiology and predictive markers. Issue 4 (11th April 2022) - Buber, Jonathan; Robertson, H Thomas
Abstract : Despite the numerous recent advancements in therapy, heart failure (HF) remains a principle cause of both morbidity and mortality. HF with preserved ejection fraction (HFpEF), a condition that shares the prevalence and adverse outcomes of HF with reduced ejection fraction, remains poorly recognised in its initial manifestations. Cardiopulmonary exercise testing (CPET), defined as a progressive work exercise test that includes non-invasive continuous measurement of cardiovascular and respiratory parameters, provides a reliable mode to evaluate for early features and for the assessment of prognostic features of both forms of HF. While CPET measurements are standard of care for advanced HF and transplant programmes, they merit a broader clinical application in the early diagnosis and assessment of patients with HFpEF. In this review, we provide an overview of the pathophysiology of exercise intolerance in HF and discuss key findings in CPETs used to evaluate both severity of impairment and the prognostic implications.